Методологія формування інформаційно-аналітичної підтримки для розвитку цифрових компетентностей бакалаврів економічного профілю - Завада, Олександр Петрович; Тоцька, Олеся Леонтіївна; Zavada, Oleksandr; Totska, Olesia Leontiivna (My University, 2021)
Стаття присвячена розробленню методології формування інформаційно-аналітичної підтримки лекційних занять для розвитку цифрових компетентностей бакалаврів економічного профілю галузей знань 05 «Соціальні та поведінкові науки» й 07 «Управління та адміністрування». У процесі дослідження визначено згідно з чинними стандартами вищої освіти України загальні та спеціальні цифрові компетентності випускників спеціальностей 051 «Економіка», 071 «Облік і оподаткування», 072 «Фінанси, банківська справа та страхування», 073 «Менеджмент», 075 «Маркетинг», 076 «Підприємництво, торгівля та біржова діяльність». Запропоновано алгоритм добору об’єктів до складу такої підтримки проведення лекційних занять з ІСТ: добір тем для викладання лекційного курсу з ІСТ у предметній сфері та їх групування у змістові модулі; визначення критеріїв добору об’єктів до інформаційно-аналітичної підтримки формування цифрових компетентностей на лекційних заняттях; добір об’єктів до кожної теми відповідно до заданих критеріїв. Критеріями добору нормативно-правових документів, які входять до складу інформаційно-аналітичної підтримки, стали актуальність, чинність, доцільність; програмного забезпечення – актуальність, національний протекціонізм, легітимність. Розроблений алгоритм апробовано на прикладі спеціальності 072 «Фінанси, банківська справа та страхування». Вказано на можливості використання пропонованої методології для викладання ІСТ студентам неекономічних спеціальностей. Окреслено альтернативи розширення інформаційно-аналітичної підтримки формування цифрових компетентностей на лекційних заняттях з ІСТ.

The need to develop digital competencies in bachelors of economics is associated with the spread of information systems and technologies (IST) into various spheres of human life, including economics and management. The purpose of the article is to develop a methodology for creating information and analytical support of lectures for the development of digital competencies of bachelors in specialties 051 «Economics»; 071 «Accounting and taxation»; 072 «Finance, banking and insurance»; 073 «Management»; 075 «Marketing»; 076 «Entrepreneurship, trade and exchange activities». The research methodology consists of the use of algorithmization, general scientific method of analysis and synthesis. The article creates an algorithm for selecting objects for information and analytical support of lectures on IST for bachelors of economics; its approbation was carried out using the specialty 072 «Finance, banking and insurance» as an example. Based on given selection criteria (relevance, validity, expediency), national legal documents (state standards, codes and laws of Ukraine, Decree of the President of Ukraine, Orders of the Ministry of Finance of Ukraine, Ministry of Economy and European Integration of Ukraine, State Treasury Service of Ukraine, Resolutions of the Cabinet of Ministers of Ukraine, National Bank of Ukraine, Board of the National Bank of Ukraine, Letter of the National Bank of Ukraine, National Classifier of Ukraine), as well as information from the official websites of domestic financial institutions and software developers were selected. Software products have been selected, for the students-financiers during lectures on information systems and technologies to be informed of their features. Alternatives to expand information and analytical support for creating digital competencies in lectures on IST are identified, such as selection of scientific, educational, teaching and methodological publications on theoretical and practical aspects of the development of digital competencies of students of a particular specialty; expansion of the analyzed software products at the expense of foreign ones; selection of educational video with visualization of work with the software of the applied sphere. The developed methodology can be used to teach IST to students of non-economic specialties, having previously changed the subject area.
Methodology for creating information and analytical support for the development of digital competencies of bachelors of economic specialty
Keywords: інформаційно-аналітична підтримка; цифрові компетентності; програмні продукти; інформаційні системи й технології; лекційні заняття; бакалаври; заклади вищої освіти; information and analytical support; digital competencies; software products; information systems and technologies; lectures; bachelors; higher education institutions; 336:004.9]:33-057.87